Ultrastrong composites from dopamine modified-polymer-infiltrated colloidal crystals1. Issue 4 (22nd July 2015) - Liaqat, F.; Tahir, M. N.; Huesmann, H.; Daniel, P.; Kappl, M.; Auernhammer, G. K.; Schneider, D.; Lieberwirth, I.; Char, K.; Fytas, G.; Butt, H.-J.; Tremel, W.
<x xml:space="preserve">Abstract</x> Multilayered nanocomposites containing iron oxide nanoparticles, strongly cemented together through a dopamine modified polymer, exhibit high resistance against elastic and plastic deformation with a Young's modulus of 17 GPa and a hardness of 1.3 GPa.